Upaya Meningkatkan Hasil Belajar Passing Bawah Bola voli melalui Penerapan Model Pembelajaran Student Teams Achievement Divisions (STAD) pada Siswa Kelas V MIN Tulungagung Tahun Ajaran 2023/2024 - Pratama, Mohammad Agung; Bekti, Ruruh Andayani; Muharram, Nur Ahmad (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The aim of this research is to improve learning outcomes for volleyball underpasses by applying the STAD learning model to Class V Students of MIN 2 Tulungagung in the 2023/2024 Academic Year. This research is Classroom Action Research (PTK). This research was carried out in two cycles, consisting of four stages in each cycle consisting of planning, implementing actions, observing and reflecting. The research subjects were Class Data collection techniques using tests and observations. The results of data analysis in cycle I, student learning outcomes increased, 23 students (96%) managed to achieve the KKM in the knowledge aspect. In Cycle I of learning volleyball underpassing, social and spiritual attitude aspects, there were 2 students (8%) who got the Very Good category, there were 19 students (79%) who got the Good category, and there were 3 students (13%) who got the Fair category. . In Cycle I of learning volleyball underpassing, aspects of volleyball underpassing skills, there were 9 students (38%) who succeeded in reaching the KKM and 15 students (62%) who had not reached the KKM. In cycle II the learning outcomes increased again compared to cycle I in learning Under volleyball passing, there were 24 students (100%) who succeeded in reaching the KKM in the knowledge aspect. In Cycle II of learning volleyball underpassing, social and spiritual attitude aspects, there were 5 students (12%) who received the Very Good (A) category, there were 19 students (88%) who received the Good (B) category. In Cycle II of learning volleyball underpassing, aspects of volleyball underpassing skills, there were 19 students (88%) who succeeded in reaching the KKM and 4 students (12%) who had not yet reached the KKM.